Paper Towns - John Green (Great Britain Bloomsbury Publishing Plc, 2010)
Quentin Jacobsen has spent a lifetime loving the magnificently adventurous Margo Roth Spiegelman from afar. So when she cracks open a window and climbs into his life-dressed like a ninja and summoning him for an ingenious campaign of revenge-he follows. After their all-nighter ends, and a new day breaks, Q arrives at school to discover that Margo, always an enigma, has now become a mystery. But Q soon learns that there are clues-and they're for him. Urged down a disconnected path, the closer he gets, the less Q sees the girl he thought he knew...
Keywords: Young Adult; Romance; Fiction; Adventure